The politics of lack in the nationalist contemporary discourse towards bicentennial Peru - Patiño-Patroni Palacios, Alexis (2021)
In recent years, the emergence of multiple crisis in the midst of the celebrations of the bicentennial have wither the nationalist discourse and politics that encouraged symbolic national fervor and identity in Peru. This study discusses a few contemporary moments of nationalist appeal, by tackling them from their mutual transitions and intertwining narrative, and by critically dismantling cultural objects of mass circulation that symbolize the nation from different ideological standpoints and affective horizons. By drawing a distinction between the historiographical studies on nationalism, which focus on the debate over perennialist approaches based on the ancestral origins of nations, and on the other hand, the modern paradigm, a constitutional and constructed national identity, I focus on the strategies and tactics through which nationalist fabrications settle in the subjectivities and in the public opinion. In particular, the attachment to identities that are affixed to psychic investments that link subjective desire and affection with the need of experiencing nationality.